PREVALENCE OF ANTERIOR OPEN BITE MALOCCLUSION IN SOUTH INDIAN POPULATION - M.Ovia; Dr.Ravindra Kumar Jain; Dr.Adimulapu Hima Sandeep (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this study was to investigate the prevalence of Anterior Open Bite Malocclusion in the South Indian population. Anterior Open Bite is a condition where there is lack of vertical overlap of upper anterior teeth with lower anteriors. It is one of the most difficult dento-facial deformities to treat. This retrospective cross-sectional study was carried at the department of Orthodontics, in a Dental College. Case records of 86,000 patients who had visited for dental treatment from july 2019 to march 2020 were assessed. Inclusion criteria for the study were presence of anterior open bite in adults . After applying the inclusion criteria 622 case records were included in the study. This data was tabulated and analysed in SPSS and descriptive statistics was performed. After photographic evaluation of records a total of 416 patients had Anterior Open Bite and among them prevalence in males was (56.5%) and females was (43.5%). Open bites of 1to2mm were very common (97.1%), than severe cases(2.9%). There was an insignificant gender association in open bite cases (p>0.05). Severity was not associated with Gender.